Impact of Manager’s Social Commitment on Organization’s Social Performance Influenced by Socially Sustainable Supply Chain Practices and Sustainability Culture - Asher Ramish; Haris Aslam; Sabtain Liaquat (Universitas Pasundan, 2021)
The social dimension of sustainability in supply chain management is significant but less prominent. This study investigates the role of a manager’s social commitment in achieving an organization’s social performance. A model with four constructs was developed to study the impact of the manager’s social commitment on social outcomes. Research was carried out on Pakistani firms through a survey-based questionnaire. From a total of 360 respondents (managers of Pakistani organizations) identified initially, 158 sent their responses after repeated follow-ups. Structural Equation Modeling was used for data analysis. The results show that socially committed managers play a significant role in achieving organization’s social performance. Furthermore, implementing social sustainable supply chain practices mediates the relationship between manager’s social commitment and organization’s social performance. This study shows that an organization’s culture promotes the implementation of social practices and helps managers adopt social responsive activities and achieve social outcomes. Additionally, this study along with theoretical support to understand the manager’s role in changing the business environment to resolve emerging social issues and improve the firm’s reputation, also provides empirical evidence from a developing country’s perspective, supported by the significant results.